MASALAH PERILAKU REMAJA MENJALANI SCHOOL FROME HOME DI ERA PANDEMI COVID-19 - Tini Tini; Andi Lis Arming Gandini (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2023)
The Covid-19 pandemic in various countries including Indonesia resulted in the Government making lock down policies and social restrictions, one of which is to work, study and worship at home. The school from home policy encourages adolescents who take formal education to replace face-to-face learning methods in class with internet-based learning at home. This is considered to have a psychological impact on adolescents. This study aims to analyze the behavior problems of junior high school students in Samarinda City while undergoing School From Home in the Covid-19 Pandemic Era. This study is a descriptive analytic study with a cross sectional approach to junior high school students and the equivalent in the city of Samarinda, selected by a multi-stage random cluster and 122 respondents using simple random sampling technique in the selected schools. The variables measured include the behavior of adolescents using the Strength and Difficulty Questionare instrument. Data were analyzed using the chi square test with a significance level of 95% (Î± = 0.05). The results showed that there were emotional problems experienced by adolescents. There is a relationship between emotional symptoms and prosocial behavior with adolescent gender (p value <0.05). Likewise, the aspects of difficulties and aspects of strength possessed by adolescents also have a relationship with adolescent gender (p value <0.05). So it is necessary to conduct coaching and monitoring of behavior in learning at least once a month.